The Role of Fintech in Increasing Investment Decisions on the Sharia Capital Market - Arinia, Syahidna; Yaser Taufik Syamlan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The digital transformation via FinTech has altered the global investment landscape, particularly the Sharia capital market. This technology provides quick access, low pricing, and inventive goods, opening up new potential for investors. However, extensive research on the impact of FinTech in improving investment decisions in the Sharia capital market from the standpoint of individual investors remains scarce. The purpose of this study is to examine the impact of age, income, environmental variables, and understanding of Sharia investment products on investing decisions made using FinTech applications. A quantitative study was conducted, including data collected from individual investors in Jabodetabek. The research was carried out utilizing Structural Equation Modeling (SEM). The findings are likely to give a thorough knowledge for FinTech developers, investors, and regulators looking to optimize the role of technology in the establishment of an inclusive Sharia finance market.